Community-Based Local Food System Development Strategy in Improving Food Security in Jayawijaya Regency Using the Analytic Hierarchy Process (AHP) Approach - tukijan; Nurul Yaqin; Vestus Febrian Aristoteles Jawan; Ayu Anggraini Tambunan (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
Food security is a condition for meeting household food needs, both in terms of quantity, quality, safety, equity, and affordability. Jayawijaya Regency, Papua, is classified as a very food vulnerable area with a ranking of 404th out of 416 districts/cities in the National Food Security Index (IKP) in 2024. This research aims to formulate an effective community-based food management strategy in improving food security in the area. The method used is the Analytical Hierarchy Process (AHP) involving 15 respondents from the community, government, and related sectors. The criteria used include economic, social, cultural, and environmental aspects. Meanwhile, alternative strategies analyzed are land optimization, food diversification, strengthening agricultural institutions, and developing community distribution. The results of the analysis showed that the land optimization strategy had the highest weight (0.494825) and was the main priority in developing food security in Jayawijaya Regency. This strategy is considered the most effective because it is able to utilize local potential optimally and sustainably.